SPECTROPHOTOMETRIC DETERMINATION OF ACETYLCYSTEINE IN PHARMACEUTICAL FORMULATIONS USING 2,3-DICHLORO-1,4-NAPTHOQUINONE - A. O. Donchenko; S. O. Vasyuk; K. P. Portna (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of research was the development and validation ofspectrophotometric method foracetylcysteine assay in pharmaceutical formulations.Тhe proposed method is based on the reaction with 2,3-dichloro-1,4-naphthoquinone and the formation of colored products that exhibit absorption maxima at 425 nm.